The impact of family history on corneal donation and transplantation attitudes: a survey-based study - Berrin Okka; Selman Belviranli; Mehmet Adam; Enver Mirza; Yasemin Durduran (Journal of the Pakistan Medical Association)
Objective: To assess how having a first-degree relative who underwent corneal transplantation influenced people’s attitudes regarding corneal donation and transplantation.